Redesain Map Rekam Medis Berdasarkan Aspek Anatomi, Fisik, dan Isi di Klinik Fisioterapi - Resta Dwi Yuliani; Suci Ariani; Herista Novia Widanti; Galuh Ratmana Hanum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Efforts to realize the implementation of good medical records require supporting elements in the form of medical record folders with a design that meets standards. Medical record folders protect patient documents and simplify the process of identifying, storing, and managing health data. Based on the results of observations at the UMSIDA Physiotherapy Clinic, the medical record folder used is still simple, only made of ordinary paper without a logo, name, clinic address, or columns for writing patient identity and medical record number. This condition has the potential to cause obstacles in the administration and security of patient data. The purpose of this research is to redesign (redesign) medical record folders based on anatomical, physical, and content aspects to make them more professional and functional. The methods used include needs analysis through interviews with users, evaluation of old designs, and the creation of new designs. The redesign was carried out by adding heading elements in the form of the name and address of the clinic, introduction in the form title or medical record folder, and instructions in the form of the text